2018
DOI: 10.1007/s40264-018-0662-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Evaluation of Additional Risk Minimization Measures for Adolescent Use of Aripiprazole in the European Union: Results from a Post-Authorization Safety Study

Abstract: IntroductionTwo risk minimization (RM) tools—a healthcare professional frequently asked questions (HCP-FAQs) brochure and a patient/caregiver information brochure (PCIB)—were developed for HCPs and for adolescents (aged ≥ 13 years) receiving aripiprazole for bipolar I mania and their caregivers.ObjectivesThis study evaluated the effectiveness of these RM tools in improving the awareness and education of HCPs and patients/caregivers.MethodThe RM tools were distributed to HCPs (identified in agreement with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
5
13
2
Order By: Relevance
“…> 20 patients), slightly higher proportions reported receipt and utilization of the aRMM tools compared with prescribers who treated ≤ 20 patients with voriconazole. This observation is consistent with the finding reported by Landsberg and colleagues [38]. We note that prescriber's general medical experience may affect aRMM awareness and utilization differently than specific experience of treating patients with voriconazole.…”
Section: Potential Reasons Behind Low Utilization Of Armm Toolssupporting
confidence: 93%
“…> 20 patients), slightly higher proportions reported receipt and utilization of the aRMM tools compared with prescribers who treated ≤ 20 patients with voriconazole. This observation is consistent with the finding reported by Landsberg and colleagues [38]. We note that prescriber's general medical experience may affect aRMM awareness and utilization differently than specific experience of treating patients with voriconazole.…”
Section: Potential Reasons Behind Low Utilization Of Armm Toolssupporting
confidence: 93%
“…In our study, most patient respondents reported receiving the PIB (77%), of which 93% reported reading it. Our results are similar to results reported in the limited number of studies identified in the literature that directly evaluated the effectiveness of RMMs with patients . Specifically, levels of receipt/reading of patient‐directed RMMs in other studies were as follows: 88%/93% (Landsberg et al), 93%/86% (Enger et al), and 89%/86% (Brandenburg et al).…”
Section: Discussionsupporting
confidence: 88%
“…Our results are similar to results reported in the limited number of studies identified in the literature that directly evaluated the effectiveness of RMMs with patients . Specifically, levels of receipt/reading of patient‐directed RMMs in other studies were as follows: 88%/93% (Landsberg et al), 93%/86% (Enger et al), and 89%/86% (Brandenburg et al). Awareness of the side effects and precautions for use of crizotinib, and reasons for contacting the physician was high for vision‐, hepatic‐, and dizziness‐related items, with knowledge levels ranging from 61% to 85%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations